Energy Balance-Related Behaviors and Body Mass Index in Asian School-Aged Children With Congenital Heart Disease. Issue 3 (May 2020) - Yang, Fu-Ling; Gau, Bih-Shya; Yang, Hsiao-Ling; Lin, Ming-Tai; Moons, Philip
Abstract : Background: Overweight/obesity is a substantial global public health concern, which can be caused by genetic factors and energy balance-related behaviors (EBRBs). If it occurs in children with congenital heart disease (CCHD), it can yield an extra burden on their health. Most studies on CCHD have taken place in Western societies, leaving Asian populations understudied, especially children. Objective: We sought (1) to determine body mass index distribution among school-aged CCHD in Taiwan, (2) to ascertain whether the body mass index of CCHD differs from that of the general population, (3) to describe EBRBs in CCHD, and (4) to identify factors associated with underweight and overweight/obesity among CCHD. Methods: In this cross-sectional study, 97 child-parent dyads (53.6% boys; mean age, 9.73 years; 25.8% moderate-to-severe heart conditions) were enrolled. Self - administered questionnaires were used to collect demographics, medical factors, food frequency, physical activity, and sedentary behaviors. Anthropometric measurements were taken in the hospital. Independent predictors of EBRBs and health conditions were calculated through logistic regression analysis. Results: Among Taiwanese CCHD, 19.6% were underweight and 14.4% were overweight/obese. Children with moderate-to-severe heart defects were more often underweight. Body mass index did not differ between CCHD and children in the general population. More complex heart defects and asthma were associated with being underweight, whereas sedentary behaviors, cardiomegaly, and the New York Heart Association classification II to IV were associated with being overweight/obese. Conclusions: Sedentary lifestyle is seemingly the only EBRB correlated with being overweight. Physical activity programs for children may help prevent and treat overweight or obesity in Asian CCHD, similar to Western countries. Abstract : Supplemental digital content is available in the text.